Tecnologia para indústria de pescado: software para gestão de processamento de tilápias - Costa, Celso Soares (2014)
The objective of this study was the development and implementation of a software for the monitoring and traceability of products and industrial processes, aiming to form thereafter a database on the production chain. We collected information about fish production chain and its industrialization and demands at the School fridge industry of UNIOESTE, in the town of Nova Prata do Iguaçu from March 2013 to March 2014. For the composition of the software, it has been used the UML methodology, which is characterized by its operability in the development of projects of the same type, thus providing a greater effectiveness. Once developed and implemented, this software has served as a tool to support the registration and the provision of data, ensuring a better efficiency in the control, storage and processing of information relevant to administrative management, generating accurate reports, as well as to provide immediate access to data registered for administrative decisions. Therefore, the application of the software contributes to an improvement in the management of the production chain of supplies, with the most important benefit: the traceability through the software indicators, with the historical of the origin and destination of the fish